Functional ecology as a missing link for conservation of a resource-limited flora in the Atlantic forest - de Paula, Luiza F. A; Negreiros, Daniel; Azevedo, Luísa O; Fernandes, Renato L; Stehmann, João Renato; Silveira, Fernando A. O (Biodiversity and conservation, 2015)
The Atlantic forest is among the hottest hotspots for biodiversity conservation. Within this biome, inselbergs are isolated granitic and gneiss rocks that rise sharply above the lowland surrounding forests. Due to prevailing stressful conditions and resource paucity of inselbergs, distinguished plant communities are formed in these rocky-associated vegetation, which comprise unusually high levels of endemic and threatened species. Here, we evaluated the importance of competitiveness:stress-tolerance:ruderalism ecological strategies in different vegetation patches on the inselberg, tested for a connection between patch structure and functional traits, and compared the variation in functional traits between native and an exotic species, which represents a major threat to inselberg communities. Despite the stressful conditions of inselbergs, we found a relatively high diversity of ecological strategies, but most species and patches lied between the S and C strategy. The invasive Melinis repens, in turn, was functionally distinctive from native communities, with the predominance of traits associated with ruderalism. We also found that most functional traits significantly correlated with at least one environmental driver, highlighting their role in structuring plant communities in this heterogeneous environment. Since inselberg patches were spatially heterogeneous, and the variation in resource availability implies in favouring different ecological strategies, some patch types were more invasive-prone than others. Our data provide significant advances for identifying the environmental drivers of biological invasion in resource-limited environments. We argue that further trait-based approaches will become critical for developing conservation and management strategies for inselberg plant communities, especially in the context of rapid habitat loss and fragmentation of the Atlantic forest.